A Noninferiority Randomized Clinical Trial of the Use of the Smartphone-Based Health Applications IBDsmart and IBDoc in the Care of Inflammatory Bowel Disease Patients. Issue 7 (23rd October 2019) - McCombie, Andrew; Walmsley, Russell; Barclay, Murray; Ho, Christine; Langlotz, Tobias; Regenbrecht, Holger; Gray, Andrew; Visesio, Nideen; Inns, Stephen; Schultz, Michael
Abstract: Background: Providing timely follow-up care for patients with inflammatory bowel disease in remission is important but often difficult because of resource limitations. Using smartphones to communicate symptoms and biomarkers is a potential alternative. We aimed to compare outpatient management using 2 smartphone apps (IBDsmart for symptoms and IBDoc for fecal calprotectin monitoring) vs standard face-to-face care. We hypothesized noninferiority of quality of life and symptoms at 12 months plus a reduction in face-to-face appointments in the smartphone app group. Methods: Inflammatory bowel disease outpatients (previously seen more often than annually) were randomized to smartphone app or standard face-to-face care over 12 months. Quality of life and symptoms were measured quarterly for 12 months. Acceptability was measured for gastroenterologists and patients at 12 months. Results: One hundred people (73 Crohn's disease, 49 male, average age 35 years) consented and completed baseline questionnaires (50 in each group). Intention-to-treat and per-protocol analyses revealed noninferiority of quality of life and symptom scores at 12 months. Outpatient appointment numbers were reduced in smartphone app care ( P < 0.001). There was no difference in number of surgical outpatient appointments or number of disease-related hospitalizations between groups. Adherence to IBDsmart (50% perfect adherence) was slightly better than adherence to IBDoc (30% perfect adherence). Good acceptability was reported among most gastroenterologists and patients. Conclusions: Remote symptom and fecal calprotectin monitoring is effective and acceptable. It also reduces the need for face-to-face outpatient appointments. Patients with mild-to-moderate disease who are not new diagnoses are ideal for this system. Clinical Trial Registration Number: ACTRN12615000342516. Abstract : This study compared 2 smartphone apps, IBDsmart and IBDoc, with standard face-to-face care. Those in smartphone app care had a reduction in face-to-face appointments and noninferior quality of life at 12 months. Gastroenterologists and patients reported good usability and acceptability.